Copper-catalyzed redox neutral ketoalkylation of Csp2–H bonds via C–C bond cleavage. Issue 20 (27th August 2021) - Chen, He; Guo, Li-Na; Sun, Qing-Xin; Chen, Lei; Tao, Jing-Qi; Gao, Pin
Abstract : An efficient copper-catalyzed ketoalkylation of Csp 2 –H bonds with cycloalkyl silyl peroxides under mild conditions is presented. A series of Csp 2 –H bonds in quinoxalin-2(1 H )-ones, heteroaromatic  N -oxides and quinones were amenable to this protocol. Abstract : An efficient copper-catalyzed ketoalkylation of Csp 2 –H bonds with cycloalkyl silyl peroxides under mild and redox neutral conditions is presented. Relying on the C–C bond cleavage, a series of distal ketoalkyl moieties were successfully incorporated into the specific position of quinoxalin-2(1 H )-ones, heteroaromatic N -oxides and quinones with moderate to good yields.